Energy-saving algorithm considering idle light-path prediction in SDM-EON - Yu XIONG; Jinyou HE; Baohua WANG; Bin ZHOU (Tongxin xuebao)
To effectively reduce the energy consumption,blocking rate and crosstalk between adjacent cores in a multi-core fiber for space division multiplexing elastic optical network (SDM-EON),an energy-saving algorithm considering idle light-path prediction was proposed.The extreme learning machine model was used to predict the traffic volume of each light-path in the network.Thus the idle light-path set and the maintenance time threshold of each idle light-path were obtained.Then,the actual maintenance time of the idle light-path was perceived by the prediction algorithm.Finally,in the light-paths where the actual maintenance time do not exceed the minimum maintenance time threshold and the inter-core crosstalk are lower than the crosstalk threshold,the idle light-path with the least loading energy consumption was selected to carry the new traffic.The simulation results show that compared with the traditional energy-saving algorithm,when the SDM-EON crosstalk limitation is satisfied,the proposed algorithm can lead better energy-saving while maintain the blocking rate at levels compatible.